2021
DOI: 10.1097/aud.0000000000001053
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Task Difficulty Predictability and Noise Reduction on Recall Performance and Pupil Dilation Responses

Abstract: Objectives: Communication requires cognitive processes which are not captured by traditional speech understanding tests. Under challenging listening situations, more working memory resources are needed to process speech, leaving fewer resources available for storage. The aim of the current study was to investigate the effect of task difficulty predictability, that is, knowing versus not knowing task difficulty in advance, and the effect of noise reduction on working memory resource allocation to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 44 publications
6
26
2
Order By: Relevance
“…The sentence baseline pupillary response was defined as the mean pupil dilation during a time interval of 1 s prior to the beginning of a sentence (Figure 1). This way of calculating the sentence baseline pupillary responses has been used in previous studies combining the SWIR test and pupillometry (Bönitz et al, 2021;Micula et al, 2021). These studies have also shown that the sentence baseline pupillary responses tend to increase over the course of several SWIR test sentences, reflecting the resources allocated to storing an increasing number of items for later recall.…”
Section: Pupillometrymentioning
confidence: 97%
See 3 more Smart Citations
“…The sentence baseline pupillary response was defined as the mean pupil dilation during a time interval of 1 s prior to the beginning of a sentence (Figure 1). This way of calculating the sentence baseline pupillary responses has been used in previous studies combining the SWIR test and pupillometry (Bönitz et al, 2021;Micula et al, 2021). These studies have also shown that the sentence baseline pupillary responses tend to increase over the course of several SWIR test sentences, reflecting the resources allocated to storing an increasing number of items for later recall.…”
Section: Pupillometrymentioning
confidence: 97%
“…A combination of behavioral and physiological measures has been used in order to investigate listening effort and cognitive resource allocation during listening tasks. Specifically, such studies often combine pupillometry with speech recognition or auditory recall test in order to investigate the effects of various manipulations, such as background noise and hearing aid signal processing (Wendt et al, 2017;Ohlenforst et al, 2017Ohlenforst et al, , 2018Zekveld et al, 2018;Bönitz et al, 2021;Micula et al, 2021). Additionally, pupillometry in combination with behavioral measures has also been used to track levels of arousal, in order to investigate the effects of time-on-task on engagement and fatigue (Hopstaken et al, 2015;Alhanbali et al, 2020;Ayasse and Wingfield, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the framework for understanding efffortful listening, it is possible that fatigue, motivation and/or the evaluation of demands on available capacity may influence the allocation of effort during recall and thereby the pupil dilation response 17. Given previous research using older adults both with and without hearing loss, we expect a speech reception threshold at 80% to load working memory without overloading its capacity, making interindividual differences in effort apparent while maintaining attentional engagement 49 55–58…”
Section: Methodsmentioning
confidence: 99%